2016
DOI: 10.1186/s12917-016-0894-2
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate threshold levels of cardiac beat-to-beat variation in semi-automatic analysis of equine ECG recordings

Abstract: BackgroundAlthough premature beats are a matter of concern in horses, the interpretation of equine ECG recordings is complicated by a lack of standardized analysis criteria and a limited knowledge of the normal beat-to-beat variation of equine cardiac rhythm. The purpose of this study was to determine the appropriate threshold levels of maximum acceptable deviation of RR intervals in equine ECG analysis, and to evaluate a novel two-step timing algorithm by quantifying the frequency of arrhythmias in a cohort o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The study by Flethøj et al showed healthy Arab horses have very narrow % R‐R variation of approximately 4% at a HR of greater than 100/min during ridden exercise . Data from our study provide similar results using a different analysis technique.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The study by Flethøj et al showed healthy Arab horses have very narrow % R‐R variation of approximately 4% at a HR of greater than 100/min during ridden exercise . Data from our study provide similar results using a different analysis technique.…”
Section: Discussionsupporting
confidence: 84%
“…Resting heart rate variability (HRV) has been well described in horses . However, during exercise, publications documenting the normal R‐R variation are limited . It is challenging during analysis of an exercising electrocardiograph (ECG) to separate truly premature beats from normal beat‐to‐beat variation, when the degree of normal variation is unclear, P‐QRS‐T morphology is difficult to differentiate and motion artifacts impair ECG quality.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Higher threshold values were applied for HRs between 60 and 100 bpm (10%) and below 60 bpm (20%). 18 Each ECG was checked manually to ensure accurate detection of the QRS complexes. Raw data were exported for HR analysis and each ECG was manually inspected for arrhythmias by two operators [S.M, R.L] as described below.…”
Section: Electrocardiographymentioning
confidence: 99%